Medication safety during anesthesia and the perioperative period / Alan Merry, Joyce Wahr. - Merry, Alan; Wahr, Joyce, 1952- (Cambridge medicine (Series), 2021)
With medication errors in healthcare an internationally recognised problem, this much-needed book delivers a comprehensive approach to understanding medication safety in the perioperative period. It reviews what medication adverse events are, and how often and where these errors occur, as well as exploring human cognitive psychology and explaining why things can go wrong at any time in a complex system. Detailed discussions around mistakes, judgement errors, slips and lapses, and violations, are presented alongside real-life examples of the indistinct line between negligence and inevitable error. The co-authors bring a wide and practical perspective to the theories and interventions that are available to improve medication safety, including legal and regulatory actions that further or impede safety. Essential reading for anesthesiologists, nurses, pharmacists and other perioperative team members committed to improving medication safety for their patients, and also an invaluable resource for those who fund, manage and regulate healthcare.